Burden of Depression and its Determinants among Tribal School-Going Adolescents in Kalvarayan Hills, Tamil Nadu - A Cross-Sectional Study - Devadharshini S; Kalaivanan R; Glannie AR; Anantharaman VV; Logaraj M (National Journal of Community Medicine, 2026)
Background: Tribal adolescents in India represent a vulnerable and under-researched population with respect to mental health. This study assessed the burden of depression and its associated factors among school-going tribal adolescents in the Kalvarayan Hills, Tamil Nadu. Methods: A cross-sectional study was conducted among 400 adolescents aged 10-19 years using multistage random sampling. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). Sociodemographic, psychosocial, and lifestyle variables were collected using a structured questionnaire. Associations were evaluated using chi-square test and multivariable logistic regression to identify independent predictors. Results: The prevalence of depression was 25.5%. Significant independent predictors included inadequate sleep, thinness, lack of parental monitoring, absence of family emotional support, peer pressure, and excessive sedentary behaviour. Sociodemographic variables such as age, gender, and socioeconomic status were not significant after adjustment. The model demonstrated good fit and acceptable explanatory power. Conclusion: A considerable proportion of tribal adolescents experience depressive symptoms, largely influenced by modifiable psychosocial and lifestyle factors. Strengthening family support systems, promoting healthy behaviours, and integrating mental health screening within school health programs are essential for early identification and intervention in this population.